THE CONCEPT OF POLITICAL PEOPLE IN THE BRAZILIAN REGENCY: REVOLUTION AND THE LANGUAGE POLICY HISTORICIZING (1831-1840) - Rauter Pereira, Luisa (Revista de Historia Social y de las Mentalidades, 2011)
The article analyses the history of the political concept of people in political debate during the Regency period in Brazilian history (1831-1840) through a theoretical perspective that seeks to understand how language and political thinking becomes historicized as a characteristic of modernity. Thus, the paper traces the incorporation of historical temporality in conceptual semantics, a phenomenon that occurred in the midst of conflicts and political debates during the formation and consolidation of the Brazilian Imperial State. The concept of people was historicized then unveiling its contingency, that is, its definition based on the analyses of present historical situation, and processual and futuristic visions of history as well. These new uses and meanings of the concept opposed to the theoretical concept of people used by liberal groups during the 7th of April Revolution (1831).